ANALYSING THE PRICE DISCOVERY FUNCTION OF CRUDE PALM OIL FUTURES (FCPO) BEFORE AND AFTER SHARI’AH-COMPLIANCE - Noryati Ahmad, (Asian Academy of Management Journal, 2015)
This paper examines the price discovery function of Malaysian crude palm oil futures (FCPO) before and after Shari’ah-compliance. The sample used in the study comprises of crude palm oil futures (FCPO) and crude palm oil (CPO) prices for the period January 2007 until December 2011. The period is divided into two sub periods: Period I (January 2007–July 2009) before Shari’ah-compliant and Period II (August 2009–December 2011) after Shari’ah-compliant. Results of Augmented Dickey Fuller (ADF) and Philips Perrons (PP) unit roots tests suggest that the CPO and FCPO series are integrated at first difference. Johansen’s co-integration test indicates that FCPO and its underlying spot market (crude palm oil) for both periods are co-integrated, implying that there is a casual relationship between the two markets. In period I, estimated results of Vector Error Correction model (VECM) during indicate one-way causality direction from CPO market to FCPO market. This can be interpreted as price discovery process that occurs from its underlying spot market to FCPO market. Further, the study observes that price discovery function of the crude palm oil futures market is increasingly more prominent after Shari’ah Advisory Board (SAC) classified the product as Shari’ah-compliant (Period II).